Kapitalisasi Teknologi untuk Siaran Budaya Jawa untuk Melayani Komunitas Urban Surabaya - Zainal Abidin Achmad; Didiek Tranggono; Ahmad Shidqi Haetami; Juliana Nur Rachmah; Salsa Billa Frisanti Sanin; A.A.I. Prihandari Satvikadewi (Department of Social Science, Faculty of Social Science &Law, Universitas Negeri Surabaya, 2023)
This study explored the use of technology in Radio Media 90.1 FM for broadcasting Javanese cultural programs to increase capital. The biggest audience for this radio is Surabaya's urban community, which loves Javanese culture. This study uses a qualitative method with a virtual ethnographic approach so that researchers can be participatory online and offline with broadcasting activities. Researchers get data about programming policies and activities of the Javanese culture-lover community at the time of the broadcast. Five informants in this study (WID, ANT, SAM, GEN, MUS representing elements of managers, programmers, broadcasters, technicians, and listeners). This study found that the technology adaptation for capitalization used is audio streaming applications and Facebook. Through the Facebook account (https://www.facebook.com/Media90.1FM), listeners build a virtual community of Javanese culture lovers. The study concludes that the interaction of the Javanese culture lover community on Facebook (viewers, likes, and comments) is a form of technology capitalization applied by radio Media 90,1 FM as data advertisers can directly utilize